Темные силы - Топильская Елена Валентиновна (Загадки следствия, 2015)
Экземпляры: ф.16 (20180522) / Инвентарный номер: 58393 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Т 58 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44